THE ROLE OF RELIGIOUS ACTIVITIES IN BUILDING GOOD CHARACTER AMONG STUDENTS AT MA ASY SYIFA IN EAST BATURAJA DISTRICT, OKU REGENCY - Eka Mustika Riantina; Fajar Nurkholik; Joni Hariyanto (LP2M IAI Al-Khairat Pamekasan, 2025)
This study aims to describe the role of religious activities in fostering students’ moral character at MA Asy-Syifa, Baturaja Timur District, OKU Regency. The research employed a descriptive qualitative approach, using observation, in depth interviews, and documentation as data collection techniques. The findings reveal that religious activities regularly implemented such as congregational prayer, Qur’anic recitation, Islamic holiday commemorations, and leadership training significantly contribute to students’ religious attitudes, discipline, and social ethics. These activities are implemented through habituation and role modeling approaches involving teachers, student religious organizations (BDI), and school leadership. Supporting factors include adequate infrastructure, high student enthusiasm, and teacher commitment. However, several obstacles remain, such as limited facilities, weak internal coordination, and low participation from some students. This study concludes that religious activities play a crucial role in developing students’ moral character, but systemic reinforcement is needed to achieve optimal and sustainable outcomes.